Dari Intoleransi Menuju Kerjasama Lintas Agama: Studi Kasus Masyarakat Muslim - Hidayat, Thaufiq (Al-Adyan: Journal of Religious Studies, 2021)
The phenomenon of religious intolerance has raised a number of problems that are not beneficial for the preservation of Bhinneka Tunggal Ika. Not only destroying the joints of unity, intolerance is also very sensitive when it comes to religious issues. However, if it refers to the social aspect, it is evident that there are several interfaith collaborations that have helped build the spirit of unity. According to the aforementioned, this paper aims to describe theoretically the portrait of intolerance transformed into interfaith cooperation, especially for Muslims. This research is a literature research using description and interpretation methods in analyzing the problem so that a conclusion can be drawn. The results of this study reveal that the transformation of intolerance into cooperation starts from intolerance to dialogue, arises from the awareness that Islam also emphasizes tolerance towards other groups so as to allow dialogue between religious adherents. Furthermore, the author places the social work dialogue model as the basis for building interfaith cooperation, as was practiced by prophet Muhammad and friends. In the last process, the dialogue continues into cooperation involving all religious adherents, such as preventing drugs, eradicating gambling, fighting alcohol, handling crime, and social support.Fenomena intoleransi agama telah banyak memunculkan sejumlah persoalan yang tidak menguntungkan bagi kelestarian bhineka tunggal ika. Tidak hanya merusak sendi persatuan, intoleransi sangat sensitif terjadi bila bersinggungan dengan masalah agama. Namun jika merujuk pada aspek sosial, maka akan terlihat beberapa kerjasama lintas agama yang turut mengkontruksi semangat persatuan. Berangkat dari hal tersebut, tulisan ini bertujuan untuk mendeskripsikan secara teoritis potret intoleransi bertransformasi menjadi kerjasama lintas agama khususnya bagi umat Islam. Penelitian ini merupakan riset kepustakaan dengan menggunakan metode deskripsi dan interprestasi dalam menganalisis masalah sehingga ditarik suatu kesimpulan. Adapun hasil penelitian ini mengungkap bahwa transfomasi intoleransi menuju kerjasama dimulai dari intoleransi ke dialog, muncul dari kesadaran bahwa Islam juga menekankan toleransi terhadap golongan lain sehingga memungkinkan terjadinya dialog antar penganut agama. Selanjutnya penulis menempatkan model dialog kerja sosial sebagai landasan membangun kerjasama lintas agama, seperti yang pernah dipraktikan oleh Rasulullah saw. dan para sahabat. Pada proses yang terakhir, dialog berlanjut ke kerjasama yang melibatkan seluruh penganut agama seperti penangkalan narkoba, pemberantasan judi, memerangi minuman keras, penanganan kriminal, dan penyantunan sosial.